Pengendalian Burkholderia glumae pada Benih Padi dengan Perlakuan Panas Kering dan Minyak Cengkeh - Kresnamurti Kurniasih; Giyanto Giyanto; Meity Suradji Sinaga; Kikin Hamzah Mutaqin; Eny Widajati (The Indonesian Phytopathological Society (Perhimpunan Fitopatologi Indonesia), 2020)
Control of Burkholderia glumae in Rice Seed by Dry Heat and Clove Oil Treatments Burkholderia glumae is a seed-borne pathogen that causes bacterial grain rot (BGR) ​disease in rice. This study aims to obtain ​disease in rice. This study aims to obtain B. glumae control techniques in rice seeds using a combination of dry heat and clove oil treatment without reducing the quality of rice seeds. This research consisted of several stages, namely: 1) preparation of healthy and infected seeds of B. glumae, 2) determination of the temperature and duration range of treatment that effectively reduced of the B. glumae population without reducing the viability of healthy seeds, 3) the effect of dry heat treatment on population B. glumae and seed viability of infected seed, 4) determination concentration of clove oil that decreases B. glumae population without decreasing seed viability of healthy seed, 5) the effect of clove oil treatment on B. glumae population and seed viability of infected seed and 6) combination of dry heat and clove oil treatment to control B. glumae in infected seed. The study showed that B. glumae population in rice seeds reduced as much as 97.68%, 98.00% dan 99.38% by dry heat treatment at 55 °C for 3, 4, and 5 hours without decreasing seed germination (seeds germination respectively 92%, 94% dan 93%). Application of clove oil 0.5% and 0.75% were able to reduce the bacterial population of 86.61% and 98.26% with the seed germination of 90.25% and 90.00%. The combination of 0.75% clove oil treatment followed by dry heat treatment at 55 °C for 5 hours eliminated all B. glumae in rice seeds without reducing the seed germination